A52 ANALYSIS AND CHARACTERIZATION OF THE EXCRETED/SECRETED PRODUCTS OF PARASITIC HELMINTHS AS IMMUNOMODULATORS OF INFLAMMATORY BOWEL DISEASE (IBD) - Siciliani, E A (J Can Assoc Gastroenterol, 2021)
BACKGROUND: Parasitic helminths Trichuris suis and Ascaris suum are known to modulate host immune responses. This is thought to be mediated by the secretome, or excreted factors released by these parasites. We are interested in the excretory/secretory products (ESP, TsESP and AsESP) and mechanisms responsible for modulating immune disfunciton in autoinflammatory diseases. AIMS: This research studies the mechanisms of immune modulation by parasitic helminths in the context of IBD. We aim to describe the cellular response in vitro, as well as the systemic response in vivo, to better characterize the scope of immune modulation in ESP treatment. METHODS: ESPs were collected from T. suis or A. suum-conditioned media and proteins and metabolites were isolated. Bone marrow (BM) derived macrophages (BMDM) from C57BL6 mice, were treated with ESP fractions, stimulated with LPS, and secreted cytokines levels measured. Alternatively, undifferentiated BM was incubated with or without metabolites throughout the process of differentiation. Using a DSS-colitis model, mice were given 3% DSS or water, then treated with ESP or PBS once daily by IP injection. Colon lengths and TNFα mRNA levels were measured and histological preparations were scored to assess pathology. ESP with bioactivity were selected for further HPLC analysis. Fractions were collected and assayed for bioactivity. RESULTS: BMDM treated with T. suis or A. suum crude ESP decreased secretion of TNFα and increased IL-10. BMDM precursors incubated with A. suum metabolites during differentiation had fewer BMDM-like cells. Cytokine analysis showed decreased TNFα secretion. Experiments with Alamar suggested that metabolites remmodelled the BMDM metabolic pathways. These effects are being explored further. We found that metabolites released by A. suum improved DSS-colitis. Specifically, mice with DSS-induced colitis given IP metabolites had reduced colon shortening compared to PBS controls, a lower histologic damage score, as well as lower levels TNFα mRNA expression in gut epithelial cells. HPLC showed multiple peaks from crudes analyzed at 210 nm and 280 nm. HPLC fractions used to treat BMDM yielded varying secretion of TNFα. Bioactive fractions from HPLC coincide with the UV/Vis peaks, further suggesting they could be isolated and studied for immunomodulation. CONCLUSIONS: These data suggested that ESP contains immunomodulators that may provide lead therapeutic compounds for patients with IBD. Helminth-derived components can immunologically polarize a response in vitro, as well as alter disease recovery in DSS colitis. HPLC fractionation and biological testing suggest that a bioactive molecule can be obtained. Further analysis must be done to determine structure using mass spectrometry and NMR analysis. FUNDING AGENCIES: Natural Sciences and Engineering Research Council of Canada (NSERC) and Fonds de recherche nature et technologies Québec (FRQNT)